2016
DOI: 10.1186/s40673-016-0057-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive brain stimulation as a tool to study cerebellar-M1 interactions in humans

Abstract: The recent development of non-invasive brain stimulation techniques such as transcranial magnetic stimulation (TMS) has allowed the non-invasive assessment of cerebellar function in humans. Early studies showed that cerebellar activity, as reflected in the excitability of the dentate-thalamo-cortical pathway, can be assessed with paired stimulation of the cerebellum and the primary motor cortex (M1) (cerebellar inhibition of motor cortex, CBI). Following this, many attempts have been made, using techniques suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…In addition to the Deymed coil producing a robust CBI response at high intensities, this coil type also reliably elicited CBI at lower intensities tolerated by participants. This is important for the field of non-invasive brain stimulation since cerebellar function is increasingly investigated with neurostimulation techniques [32,33] and stimulation itself is commonly reported as uncomfortable. These findings, therefore, present an alternative and more comfortable option for future research designs involving both healthy and neurological patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the Deymed coil producing a robust CBI response at high intensities, this coil type also reliably elicited CBI at lower intensities tolerated by participants. This is important for the field of non-invasive brain stimulation since cerebellar function is increasingly investigated with neurostimulation techniques [32,33] and stimulation itself is commonly reported as uncomfortable. These findings, therefore, present an alternative and more comfortable option for future research designs involving both healthy and neurological patients.…”
Section: Discussionmentioning
confidence: 99%
“…Following on animal models of cerebellar physiology (Ohyama et al, 2003 ; Ohmae and Medina, 2015 ; Giovannucci et al, 2017 ), there is a nascent implementation of cerebellar tACS in investigations of human motor function (Tremblay et al, 2016 ). Importantly, cerebellar neurophysiology excludes recurrent excitatory loops (Buzsáki, 2006 ; Rokni et al, 2008 , 2009 ; Duguid et al, 2015 ).…”
Section: Target and Task-specific Tacsmentioning
confidence: 99%
“…In further support of the physiological data, computational modeling studies have confirmed that exogenous weak electric currents at an intensity of 2 mA can reach the outer layers of the cerebellar cortex [ 10 ]. The possibility to non-invasively target the human cerebellum with tDCS introduces new opportunities to study its role in motor and also non-motor functions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%